2006
DOI: 10.1002/neu.20270
|View full text |Cite
|
Sign up to set email alerts
|

Physiological requirement for the glutamate transporter dEAAT1 at the adult Drosophila neuromuscular junction

Abstract: L-glutamate is the major excitatory neurotransmitter in the mammalian brain. Specific proteins, the Na+/K+-dependent high affinity excitatory amino acid transporters (EAATs), are involved in the extracellular clearance and recycling of this amino acid. Type I synapses of the Drosophila neuromuscular junction (NMJ) similarly use L-glutamate as an excitatory transmitter. However, the localization and function of the only high-affinity glutamate reuptake transporter in Drosophila, dEAAT1, at the NMJ was unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 66 publications
6
51
0
Order By: Relevance
“…This mimics the effects we observed with acute pharmacological manipulations of glutamate transport, and resembles a published report on mutants of the AMPA-type glutamate receptor KaiRIA (also known as GluR-IID or brec) (Featherstone et al, 2005). Second, Eaat1 has been reported to be absent from neuromuscular junctions in larvae (Rival et al, 2006). Third, crawling was rescued with a Gal4 driver expressed exclusively in CNS glia.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This mimics the effects we observed with acute pharmacological manipulations of glutamate transport, and resembles a published report on mutants of the AMPA-type glutamate receptor KaiRIA (also known as GluR-IID or brec) (Featherstone et al, 2005). Second, Eaat1 has been reported to be absent from neuromuscular junctions in larvae (Rival et al, 2006). Third, crawling was rescued with a Gal4 driver expressed exclusively in CNS glia.…”
Section: Discussionsupporting
confidence: 84%
“…Previous approaches using RNAi had uncovered no function for Eaat1 in larvae (Rival et al, 2004;Rival et al, 2006); this is likely due to insufficient knockdown at larval stages since here we found Eaat1 mutants have a severe crawling deficit. We narrowed the requirement for this glutamate transporter to a subpopulation of CNS glia and found that the crawling defect could be induced by conditional inactivation of Eaat1 after embryogenesis.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The known lethality of null mutations in Eaat1 (Stacey et al, 2010) and pronounced phenotypes in flies with pan-glial-cell RNAi knockdown of Eaat1 (repo-GAL4) (Rival et al, 2004;Rival et al, 2006) led us to test alrm-GAL4> Eaat1 RNAi larvae for gross locomotor defects. We did not detect any changes in contraction rate (mean +/− SD contractions per minute = 40.2 +/− 20.0 for UAS Eaat1 RNAi controls, 46.6 +/− 10.5 for alrm-GAL4 controls, and 41.2 +/− 13.1 for alrm-GAL4> Eaat1 RNAi ; n = 7 in each group, n.s.).…”
Section: Astrocyte Glutamate Transport Is Mediated By Eaat1mentioning
confidence: 99%
“…Given this cellular phenotype, it is somewhat surprising that the larvae exhibit grossly normal locomotion and development. In contrast, flies carrying null mutations in Eaat1 do not survive beyond the first-instar larval stage (Stacey et al, 2010), and those with pan-glial-cell RNAi knockdown of Eaat1 (repo-GAL4) are viable but exhibit a shortened lifespan, neuropil degeneration, and locomotor phenotypes (namely, they can walk but cannot fly; Rival et al, 2004;Rival et al, 2006). This is unexpected given that Eaat1 immunolabeling is localized almost entirely to astrocytes; and alrm-driven RNAi knockdown eliminates any detectable labeling.…”
Section: Glutamate Transporter Currents Are Mediated By Eaat1mentioning
confidence: 99%